Digital Technology And The Resilience Of Micro, Small, And Medium Enterprises (MSMEs) During The Covid-19 Pandemic: A Literature Review And Policy Analysis In The Indonesian Context - Kurniawan, Ihsan (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
The COVID-19 pandemic has significantly impacted the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, both in terms of declining market demand and operational disruptions. In response to these challenges, the adoption of digital technology has emerged as a crucial strategy for business continuity. This article aims to examine the critical role of digital technology in enhancing the resilience of MSMEs during the pandemic through a literature review and public policy analysis. Using a descriptive qualitative method, this study draws on scientific journals, government reports, and policy documents published between 2020 and 2024. The findings indicate that digital platforms such as e-commerce, social media, and financial technology applications have effectively supported MSMEs in sustaining their operations. Furthermore, government initiatives including the "Proudly Made in Indonesia" National Movement (BBI), digital onboarding training programs, and collaborations with digital ecosystems have accelerated the digital transformation of the MSME sector. Nevertheless, several barriers persist, including low digital literacy, limited infrastructure, and unequal access to technology, which hinder the full optimization of digitalization. This study offers inclusive and sustainable policy recommendations to strengthen MSMEs in the post-pandemic digital era.